2009
DOI: 10.1097/pas.0b013e3181a95c63
|View full text |Cite
|
Sign up to set email alerts
|

NK-cell Lineage Predicts Poor Survival in Primary Intestinal NK-cell and T-cell Lymphomas

Abstract: Most primary intestinal natural killer (NK)-cell and T-cell lymphomas (PINKTL) in the Northern Europe are enteropathy-associated T-cell lymphomas, a complication of celiac disease, which is rare in the East. Primary intestinal NK-cell lymphoma is extremely rare and is poorly characterized. We investigated 30 cases of PINKTL from Taiwan with male: female at 2:1, median age at 55.5, 80% with jejunal/ileal involvement, 77% with perforation, 27% with multicentric tumors, and 67% at stage IE. All 7 cases tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 39 publications
5
89
1
Order By: Relevance
“…males (mean age 37 years), and the lymphomas were more likely to arise in the colon. As same as previous reports, 7,16 primary intestinal NK-cell lymphoma in our study had a higher incidence of intestinal perforation and was more likely to cause systemic symptoms such as fever compared with the T-cell group. In 2008, Tung et al 17 reported five primary intestinal NK-cell lymphomas based on EBER positivity and polyclonal T-cell receptor gene rearrangements using conventional clonality studies in a series of 11 primary intestinal T-cell and NKcell lymphomas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…males (mean age 37 years), and the lymphomas were more likely to arise in the colon. As same as previous reports, 7,16 primary intestinal NK-cell lymphoma in our study had a higher incidence of intestinal perforation and was more likely to cause systemic symptoms such as fever compared with the T-cell group. In 2008, Tung et al 17 reported five primary intestinal NK-cell lymphomas based on EBER positivity and polyclonal T-cell receptor gene rearrangements using conventional clonality studies in a series of 11 primary intestinal T-cell and NKcell lymphomas.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, seven tumors were considered type II enteropathy-associated T-cell lymphoma, accounting for 16 and 22% of the primary intestinal T-cell and NK-cell lymphoma and T-cell groups, respectively. These percentages are higher than those reported by Chuang et al, 16 who found only 2 type II enteropathy-associated T-cell lymphoma cases among 30 primary intestinal T-cell and NK-cell lymphomas.…”
Section: Discussioncontrasting
confidence: 66%
“…This observation is consistent with a recent study of EATL in 18 Chinese patients, which also showed only type II histology [10]. In several previous studies of intestinal T-cell lymphomas in Asian patients [6][7][8][9]11,12,17,18], type II EATL was also predominantly observed, although fewer than 10 cases of apparently classical EATL were described. However, the diagnosis of classical EATL in these few cases had been queried, based on the lack of stringency in diagnosis, doubtful histologic features, and immunophenotypes that would in fact be consistent with type II EATL [10].…”
Section: Discussionsupporting
confidence: 92%
“…However, the clinical, histolopathologic, and immunophenotypic features of these cases were really indistinguishable from other EBV-negative cases and to classify these cases as PTCL-NOS simply because they were EBV-positive might not be justified. Interestingly, EBV positivity has also been reported in intestinal T-cell lymphomas in other Asian patients [7]. The presence of EBV infection in a small fraction of type II EATL warrants further investigations into its pathogenetic significance.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation